Benefits of personal music listening for family caregivers of critically ill patients during the post-COVID era - Yoo, Ga Eul; Na, Sungwon; Kim, Soo Ji; Kim, Jeongmin (Frontiers in Psychology, 2023)
Objective This descriptive study surveyed family caregivers of patients in intensive care units (ICUs) during the COVID-19 pandemic to examine the impact of musical listening on their psychological well-being. Method The data collected in this study compared with collected from similar research conducted before the COVID-19 pandemic in 2017. The previous study had 195 participants, and the current study had 92. To measure the participants’ psychological well-being, the Korean version of the Center for Epidemiologic Studies Depression Scale and the World Health Organization Quality of Life Scale were administered. An investigator-constructed questionnaire was also used to collect information related to participants’ engagement in music activities including music listening in their everyday lives and their perceptions of music’s benefits. Results A two-way ANOVA showed significant effects for time (e.g., before vs. during COVID-19) and involvement in personal music listening (yes vs. no) on current emotional state, with family caregivers reporting significantly greater negative emotions during COVID-19 than before and personal music listening having a positive effect on perceived emotions. For quality of life there was no significant time effect, while the listening effect was statistically significant, indicating a significantly higher quality of life in the group who engaged in music listening in their everyday lives compared to the group who did not. There were no significant time or listening effects for perceived level of depression. Conclusion Given the COVID-19 situation and the need to transition to a post-pandemic era, this study suggests that music listening can be an effective option for family caregivers to implement as a resource for attenuating emotional distress and enhancing self-care.